Change resistance in central government organisations in Jordan: Causes and implications for future trends of administrative reform and development - Khassawneh, Anis (2002)
The main objective of this study is to investigate the causes of employees' resistance to administrative changes in bureaucratic organizations in Jordan. it has been found that the lack of employees' participation, inadequate incentives, mistrust between employees and higher management, lack of clarity in the goals of change stand, in order, as the five highest causes of resistance to administrative change. Resistance causes pertaining only to employees' participation, incentives and mistrust of higher management reported significance relationships with two or more of respondent's background variables. Based on these findings short and long-term implications for future trends of administrative reform and development in Jordan are explicated. - Reproduced.
Keywords: Central Government - India; Administrative reform - Jordan; Administrative reform